Blumgart versus conventional anastomosis for pancreatojejunostomy after pancreaticoduodenectomy - What will we choose? (Journal of Surgical Sciences, 2025)
Background: Pancreatic leakage is a major cause of postoperative mortality and morbidity after pancreaticoduodenectomy (PD). A recent study introduced Blumgart anastomosis (BA), which minimizes severe complications after PD. This study compares BA with conventional anastomosis (CA) for pancreaticojejunostomy (PJ) after PD in the Department of Surgical Gastroenterology, Sheikh Russel National Gastroliver Institute and Hospital.  Methods: This retrospective observational study includes 20 patients who underwent PD between November 2020 to November 2021. The patients were divided into two groups according to the anastomosis type. Of them, 10 patients underwent anastomosis using CA (group A, conventional anastomosis including Dunking and Duct to mucosa) and 10 underwent anastomosis using BA (group B, Blumgart anastomosis). The methods were compared in context of postoperative pancreatic fistula (POPF), post pancreatectomy hemorrhage (PPH), and delayed gastric emptying (DGE) to see the overall outcome of two techniques.  Results: Mean duration of operation time was significantly shorter in group B (373.1±102.0 versus 256.4±58.5 min, p